Estudo da adição de silicato de sódio alcalino em componentes cimentícios - Fonseca, Juliana Maria Mccartney da (2021)
Sodium silicate Na2O(SiO2)n is an inorganic compound that has been widely used in civil construction, mainly in the area of geotechnical stabilization, surface blockers (waterproofing), and as an alkaline activator in slag cements. Although the mechanisms that involve the interaction of sodium silicate and Portland cement, in the period of hydration, curing and hardening are not completely elucidated, it is assumed that the efficiency of this product occurs through the pozzolanic effect by the reaction between sodium silicate and calcium hydroxide, giving rise to hydrated calcium silicate (C-S-H). Therefore, this research aims to analyze the influence of the addition of different levels of alkaline sodium silicate on the microstructural characteristics of fresh and hardened pastes, as well as the mechanical properties of mortars under different water/cement ratios, cures and ages. The results showed that sodium silicate can influence the cementitious properties, according to the water/binder ratio, in a range of silicate percentiles.